Effects of Free-Range Systems on Muscle Fiber Characteristics and Welfare Indicators in Geese - Guoyao Wang; Jianzhou Chen; Yujiao Guo; Kaiqi Weng; Yu Zhang; Yang Zhang; Guohong Chen; Qi Xu; Yang Chen (Animals)
Recently, free-range poultry production has increased with notable benefits for animal welfare and meat quality traits. Geese, the third-most productive poultry species, have not been studied extensively. This study investigated the effects of different free-range systems on muscle fiber characteristics and welfare status (feather quality, walking ability, and behavioral changes) in Yangzhou geese. A total of 180 male geese, aged 28 days, were randomly assigned to either a long-distance pasture system (LDPS, approximately 200 m from the geese house) or a short-distance pasture system (SDPS, approximately 50 m from the geese house). The indoor system (IS) treatment was used as a control. And all geese were equipped with pedometers. Daily step counts revealed that the geese took an average of 5777 and 4520 steps in the LDPS and SDPS, respectively, whereas only 2736 steps in the IS. Although no significant differences were observed in the muscle fiber types among the three systems, free-range systems contributed to more developed muscle fibers than the IS. In addition, thicker muscle fibers in the extensor digitorum longus and gastrocnemius muscles were observed in the LDPS group than in the SDPS group. Additionally, feather cleanliness and damage were evaluated. LDPS resulted in significantly cleaner feathers on the chest, abdomen, and back than the IS. Furthermore, geese in the free-range systems had less feather damage than those in the IS. Notably, pasture systems allowed for natural behaviors, such as single-foot standing, feather pecking, and walking, regardless of grazing distance. Taken together, these results show that the muscle fibers of geese in the free-range system were more developed. Simultaneously, increasing the amount of exercise for geese will improve their welfare, which is beneficial to their health, growth, and development, and provides a technical reference for the free-range breeding system for geese.